Judah Halevi, religious thinker and poet : comparative study of his "Kuzari" and poetry - Lamdan, Hertzel (Department of Religious Studies, 2015)
This is the first attempt at a comparative study in which Judah Halevi's main ideas and teachings as they find expression in his philosophical work "The Kuzari" are compared and contrasted with their treatment in his poetical work. We feel that such a contrasting and comparative study may bring us nearer to a more comprehensive understanding of the creative personality of the author in all its facets and to a fuller understanding of his ideas on various subjects, than the consideration and study of just one aspect of his creative work, either poetry or philosophical thought, would. Poetry and philosophy could complement each other; emotion and poetic expression will in this study complement the intellect and rational ideas, and vice versa.